MORFOLOGI POLEN VEGETASI MANGROVE DI DESA SALO PALAI KEC. MUARA BADAK KAB. KUTAI KARTANEGARA - Yuliana, Titin; Syafrizal, Syafrizal; Hariani, Nova (Jurnal Pendidikan Matematika dan IPA, 2018)
This study aims to identified pollen morphology of Mangrove vegetation in Salo Palai Village, Muara Badak Sub District, Kutai Kartanegara District was done in May until July. This study using acetolisis method. Data obtained were analyzed with qualitative descriptive method to observed the shape, ornaments and also aperture. This method is measuring size, the length of the polar axis to the equatorial diameter. The result obtained shape and pollen unit is monad subspheroidal. There are size medium pollen and size large pollen. The ornaments including of 7 psilate, 2 reticulate and 2 ekinate. The aperture including of 4 inaperture, 2 tricolporate, 1 tricolpate, 1 triporate, 1 tetraporate, 1 monoporate and 1 stephanocolporate.Keywords: Vegetation, Mangrove, Pollen, Association, Identification.